2016
DOI: 10.1139/cjp-2015-0495
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation of massive vector particles from a warped AdS3 black hole

Abstract: Hawking radiation (HR) of massive vector particles from a rotating Warped Anti-de Sitter black hole in 2+1 dimensions (WAdS3BH) is studied in detail. The quantum tunneling approach with the Hamilton-Jacobi method (HJM) is applied in the Proca equation (PE), and we show that the radial function yields the tunneling rate of the outgoing particles. Comparing the result obtained with the Boltzmann factor, we satisfactorily reproduce the Hawking temperature (HT) of the WAdS3BH.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In this paper, the Hawking temperature is discussed for three coordinate systems. Gursel and Sakalli [17] studied the Hawking radiation of massive vector particles from rotating warped anti-de Sitter BH in 3D and showed that the radial mapping gives the tunneling rate for outgoing particles. Different authors [18,19] have found the Hawking temperature for various types of particles from BHs.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the Hawking temperature is discussed for three coordinate systems. Gursel and Sakalli [17] studied the Hawking radiation of massive vector particles from rotating warped anti-de Sitter BH in 3D and showed that the radial mapping gives the tunneling rate for outgoing particles. Different authors [18,19] have found the Hawking temperature for various types of particles from BHs.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, various methods have been proposed to calculate the temperature of a black hole known as Hawking temperature. On the other hand, the Hamilton-Jacobi approach is an important version of the tunnelling method of the quantum mechanical point-like particles from a black hole [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Adopting this approach, Hawking temperature of various black holes were recovered by quantum tunnelling method of the particles across their event horizons.…”
Section: Introductionmentioning
confidence: 99%
“…A reader would appreciate that the most subtle black holes are the rotating ones defined in the higher dimensions. From this viewpoint, we aim to extend the Kruglov's studies (and his followers' works [54][55][56][57][58][59][60][61][62][63][64][65]) to the radiation spectrum of massive vector particles spraying from a 5-dimensional Kerr-Gödel black hole (5DKGBH). Thus, we aim to calculate Hawking temperature [66] of the 5DKGBH.…”
Section: Introductionmentioning
confidence: 99%